The negative impact of squad rotation on football match outcomes: Mediating roles of passing and shooting performance - Yang, X.; Zhou, C.; Xu, Z.; Yan, D.; Ruano, M. A. G. (Journal of Sports Sciences, 2025)
This study examines the impact of squad rotation on match outcomes in professional football while analysing the mediating role of technical and physical indicators. Using data from the 2021 Chinese Super League (CSL), we analysed 236 match records from 118 matches played under congested schedules (=96 hours between games). Principal Component Analysis (PCA) reduced 30 performance indicators to eight principal components (PC). Bootstrap mediation analysis further explored the relationships between rotation, PCs, and match outcomes. The results indicate that increased squad rotation negatively affected match outcomes, with passing (PC2) and shooting performance (PC3) mediating this effect. Specifically, each increase in Rotation3 reduced the probability of winning by 6.4%, with passing performance explaining 11.9% of this effect. A 0.1 increase in Stability1 was associated with a 6.8% higher probability of winning, with passing performance accounting for 9.8% of this effect and shooting performance for 12.0%. These findings underscore the negative impact of excessive rotation on match performance. Coaches are advised to minimise rotations during critical matches while ensuring player health through data-driven strategies and collaboration with medical staff.